an Exploration of Plant Water Extracts in Environmentally Friendly Bioherbicide Innovation: A Literature Review: Eksplorasi Ekstrak Air Tanaman dalam Inovasi Bioherbisida Ramah Lingkungan: Suatu Tinjauan Literatur - Susilo, Edi; Pujiwati, Hesti; Rita, Wismalinda (Agriculture, 2025)
The use of synthetic herbicides in agriculture raises many problems, including weed resistance, ecological damage, and health risks. To address these issues, plant-based biological herbicides have been introduced as a safer and more sustainable alternative. This study focuses on plants that exhibit allelopathy, including those that contain phenolic compounds, flavonoids, terpenoids, alkaloids, and tannins, which have the potential to be compact and phytotoxic to weeds through various mechanisms, including inhibiting germination, root growth, cell respiration, and photosynthesis, and disrupting hormonal balance. Therefore, various water-extraction techniques, such as soaking, boiling, and maceration, were studied to obtain the maximum amount of bioactive compounds. Plants that produce potent phytotoxic compounds, including Sorghum bicolor, Ageratum conyzoides, Chromolaena odorata, Mikania micrantha, Azadirachta indica, and Tagetes erecta, have been tested to contain active compounds that are effective in suppressing the growth of various weeds. Adaptation and development of bioherbicides made from water-extract compounds in the field of research, although promising, also face various challenges, including degradation of the active compounds, variations in raw materials, low extract concentrations, and the need for standardization in extraction methods and formulations. Therefore, characterization techniques for potentially allelopathic materials, more sophisticated formulations such as microencapsulation and nanoformulation, and investigation of potentially synergistic compounds between plant extracts and beneficial microorganisms are needed. This study confirms that plant water extracts have great potential as environmentally friendly weed-control solutions that support sustainable agricultural systems.